Designing for accountability from Islamic perspectives using value sensitive design / Fadzlin Ahmadon, Rosmawati Nordin and Rashidah Md Rawi - Ahmadon, Fadzlin; Nordin, Rosmawati; Md Rawi, Rashidah (Penerbit UiTM, 2014)
The value of accountability is important to the stakeholders of HUSM Psychology Clinic and is compromised with the current system in use. A change to the system in use is essential in order to support this value. Value Sensitive Design (VSD) is a design approach that focused on how moral values can be embedded in a system. Due to this feature, VSD is chosen as a design technique to develop a new system for the clinic. In order to define what accountability means and how it can be designed, studies were done on Islamic sources of Qur'an and Sunnah of the Prophet Muhammad in addition to definition by mainstream ethicists and works on system design literatures. The result is a system that employs design strategies that support the value of accountability. The works in this paper shows that it is possible to refer to Islamic traditions as a point of reference for designing ethical information system. This work can be expanded in the future by having more design suggestions based on Islamic sources for other values and issues especially those concerning the Muslim society.